Does Temporary Affirmative Action Produce Persistent Effects? A Study of Black and Female Employment in Law Enforcement - Miller, Amalia R.; Segal, Carmit (The Review of Economics and Statistics, 2012)
This paper exploits variation in the timing and outcomes of employment discrimination lawsuits against U.S. law enforcement agencies to estimate the cumulative and persistent employment effects of temporary externally imposed affirmative action (AA). We find that AA increased black employment at all ranks by 4.5 to 6.2 percentage points relative to national trends. We also find no erosion of these employment gains in the fifteen years following AA termination, although black employment growth was significantly lower in departments after AA ended than in departments whose plans continued. For women, in contrast, we find only marginal employment gains at lower ranks.